Nitrogen Utilisation of Lowland Cauliflower Grown on Coconut Coir Dust - Ahmad, Asiah (2003)
Strong wind, high rainfall, the spread of diseases during rainy season and pests problems in open field agriculture have led to the current trend in growing vegetables under protected environment. The occurrence of soil borne disease, and limited suitable land for agriculture are some of the reasons to look for alternative media such as coconut coir dust. The basic properties of coconut coir dust as a soilless growing medium and the utilisation of nitrogen (N) fertiliser for the lowland cauliflower grown in them have not been thoroughly investigated and are therefore not well understood. This study has been conducted by the need to provide a basis for determining optimal levels/concentration and forms of nitrogen supply, and by the need to minimize environmental consequences of lowland cauliflower production. It focuses on the effects of N supply in terms of different levels of N and ionic N forms in the nutrient solution, on the growth, development and N utilisation of cauliflower grown in coconut coir dust under greenhouse condition in the lowlands. Based on the plant growth parameters studied coconut coir dust was found to be more suitable than oil palm empty fruit bunch as a growing medium. From the growth and development study using coconut coir dust, it can be deduced that the N requirement by the plant is less at later growth stage regardless of low or high level of N in the nutrient solution. However, low level of N of 50 mg r1 was found to be inadequate for plant growth and curd yield.